Mau Funcionamento do Sistema de Circulação Extracorpórea: Relato de Caso - De Almeida, Carlos Eduardo David; Carraretto, Antônio Roberto [UNESP]; Curi, Erick Freitas; Marques, Louisie Marcelle da Silva Almeida; Abatti, Roberta Eleni Monteiro (Elsevier, 2011)
Background and objectives: The introduction of extracorporeal circulation in clinical practice was decisive for the development of modern cardiovascular surgery. Addition of new procedures and equipment, however, brings inherent risks and complications. The objective of this report is to describe a malfunction of the oxygenation system and emphasize the importance of the interaction among the medical team members to prevent errors and complications. Case Report: During valve replacement and IVC correction surgery, we observed a darker shade of red in the blood on the exit of the oxygenator. Laboratory tests demonstrated severe acidosis and hypoxemia. The entire system was evaluated, but the cause of the malfunction was not found. Measures to reduce damage were successfully instituted. After the surgery, the whole system underwent technical evaluation. Conclusions: Interaction among the medical team members, early diagnosis, and immediate intervention were fundamental for a favorable outcome. © 2011 Elsevier Editora Ltda.
Malfunction of the extracorporeal circulation system: Case report
Keywords: Accident Prevention; Extracorporeal Circulation; Intraoperative Complications; fentanyl; isoflurane; midazolam; pancuronium; propofol; sufentanil; thiopental; acidosis; adult; aorta valve regurgitation; arterial gas; case report; continuous infusion; extracorporeal circulation; heart valve replacement; human; hypothermia; hypoxemia; lung circulation; lung ventilation; male; oxygenator; patient monitoring; pericardiotomy; peroperative complication; respiratory arrest; shunting; Equipment Failure; Humans; Male; Middle Aged